Design and Development of a Vision System Interface for Three Degree of Freedom Agricultural Robot - Omrane, Bouketir (1999)
In this study, a vision system interfaced 3DOF agricultural harvester robot was designed, developed and tested. The robot was actuated by hydraulic power for heavy tasks such as picking and harvesting oil palm FFB. The design was based on the task of that robot, the type of actuators and on the overall size. Attention was given to the stability, portability and kinematic simplicity in relation to the hydraulic actuators. The derivation of the kinematic model was based on the Matrix Algebra for the forward kinematics, and the inverse kinematics problem was based on analytical formulation. The D-H representation was used to carry out the coordinates of the end-effector as the function of the joint angles. The joint angles of the robot were computed as the function of the end-effector coordinates to achieve the inverse kinematic model. A mathematical model that related the joint angles and the actuators length was derived using geometric and trigonometric formulations. A differential system was derived for the manipulator. This differential system represents the dynamic model, which describes relationships between robot motion and forces causing that motion. The Lagrange-Euler formulation with the D-H representation was applied to formulate the differential system. The importance of the derivation of the kinematic model arises in the development of the control strategy. While the derivation of the dynamic model helps in real time simulation. The robot was enhanced by a CCD camera as a vision sensor to recognise red object as a target. Red object was to exemplify the matured oil palm FFB . The recognition process was achieved by using C++ programming language enhanced by MIL functions. An algorithm based on empirical results was developed in order to convert the target coordinates from the image plane (pixel) into the robot plane (cm). The image plane is two-dimensional while the robot plane is three-dimensional. Thus at least one coordinate of the target in the robot plane should be known. An Interface program has been developed using Visual Basics to control and simulate 2D motion of the manipulator.